Las Españas : revista literaria / [editores: Manuel Andújar, José Ramón Arana y José Puche Planas] - Andújar, ManuelArana, José Ramón (1905-1973) Puché Planas, JoséMartín Nájera, AurelioCarretero y Jiménez, Anselmo
Incluye suplemento "Antonio Machado"Editor Anselmo Carretero y Jiménez desde nov. de 1947 | Reprod. facs. de la ed. de: México : Las Españas, 1946-1956